Hoax News and Digital Skills through the Application Hoaks Booster Tools - Marlina (Budapest International Research and Critics University, 2022)
This study, which aims to determine the extent of knowledge and skills of MAN 1 Mandailing Natal students regarding hoax news and its distribution, was conducted at MAN 1 Mandailing Natal. By involving 45 students, with the criteria of having and active users of observation and interviews. The results of this study indicate that skills in media literacy are a perspective that can be used by a person when he is carrying out activities related to media, in interpreting the meaning of a message received from various sources. Building a perspective that is carried out by someone based on a knowledge structure that is constructed from the ability to use existing information. From the results of research conducted on 45 students, various data were obtained, especially the data section social media for news search, not only for eintertein use. This study uses qualitative research methods with data collection methods through regarding technical skills. There are 28% of students who daily get information on the internet and 30% use the information on the internet to then view and read and share information.